(untitled) (Swiss Medical Weekly, 2011)
OBJECTIVE:To describe the clinical features and outcomes of hospitalised cases of the 2009 influenza A H1N1 virus infection at Geneva’s University Hospital during the peak of the epidemic. METHODS: From October 2009 to January 2010, we conducted a four-month prospective case collection of H1N1 laboratory confirmed cases and subsequently reviewed all medical charts of the patients admitted at Geneva’s University Hospital. RESULTS: During the data collection period, 1336 subjects with influenza-like illness were tested for the 2009 H1N1 in Geneva and 451 were positive (34%). A total of 85 patients with confirmed H1N1 were hospitalised (56 adults and 29 children). Patients’ median age was 39 years (range 1 month–94years) and the mean hospital length of stay was 12 days. Conditions promoting influenza complications were present in 59% of patients and were mainly asthma, chronic obstructive pulmonary disease (COPD), haematologic disorders and immunosuppressive treatment. The most common reported symptoms were cough, fever, dyspnoea and rhinopharyngitis. Most of the patients (n = 72, 85%) were treated by neuraminidase inhibitors, and 44% (n = 37) received antibiotics for secondary bacterial infection. Fourteen patients (11 adults and 3 children, 16%) developed respiratory failure and were admitted to the intensive care unit (ICU) for respiratory monitoring and/or ventilatory support. The mean ICU length of stay was 11.3 days. The mortality rate was 2.5% among all patients. CONCLUSIONS:Geneva’s experience of the 2009 H1N1 pandemic showed that most of the hospitalised patients were young adults or children. Half of them presented predisposing diseases but only 16% were admitted to the ICU. The mortality rate was low.